AN ANALYSIS ON RELATIVE CLAUSE IN âBRIDGE TO TERABITHIAâ NOVEL - Kadariyah, Nurlaila; Purwanti, Desy (English Department of Faculty of Tarbiyah and Teachers Training, 2013)
This research describes 1). Tthe original sentences of relative clause in novel bridge to Terabithia; (2) Tthe common relative clause found in the novel; (3). Â The frequency of kinds of relative clause that are used in the novel. The subject of this research is novel âBridge to Terabithiaâ by Katherine Paterson and the object of this research is relative clause in novel âBridge to Terabithiaâ by Katherine Paterson. The data of this research are collected through reading and comprehending the story of novel, choosing the data dealing with the problem of the study, and conducting survey on novel script. Then taking evidences related to the question from the selected data. All collected data are then processed systematically through editing and clarifying. The result of the research shows that there are five patterns of relative clause found in the novel âBridge to Terabithiaâ by Katherine Paterson namely relative clause of who, whom, whose, that and which. First, the most frequently appeared in this novel are 99 relative clause of that, the second position Â Â Â are 39 relative clause of who. After that in the third position Â Â are 26 relative clause of which, in the forth position Â Â are 5 relative clause of whose. The last in the fifth Â Â are 3 relative clause of whom.